Interaction between Time Budget Pressure and Professional Commitment towards Underreporting of Time Behavior. (31st May 2016) - Andreas,
Abstract: The escalation of auditor's digress behavior increased sharply as time budgets were seen to approach. The purpose of this study is to investigate the moderating effect of time budget pressure on the relationship between professional commitment and underreporting of time behavior. This study was conducted using a survey on auditors who work in the second tier of accounting firm in Indonesia. The findings indicated that: (1) all dimensions of auditors' professional commitment significantly gives a positive effect on the underreporting of time; and (2) perceived time budget pressure strengthens the influence of all dimensions of auditors' professional commitment towards underreporting of time. These findings suggest that firm should evaluate the auditor's commitment to improve audit quality.